Complexation between whey protein and octenyl succinic anhydride (OSA)-modified starch: Formation and characteristics of soluble complexes. (October 2020) - Wu, Dan; Lin, Quanquan; Singh, Harjinder; Ye, Aiqian
Graphical abstract: Highlights: Complexation between whey protein and octenyl succinic anhydride (OSA)-modified starch. OSA modified starch tended to interact with heated whey protein. Soluble complexes were formed between heated whey protein and OSA-modified starch. Degree of substitution of OSA-modified starch affects the properties of the complexes. MW of OSA-modified starch affects the properties of the complexes. Abstract: Mixed systems of protein and polysaccharide are widely used in the food industry. It is important for food manufacturers to understand their interactions. In this study, the formation of complexes between whey protein isolate (WPI) and octenyl succinic anhydride (OSA)-modified starch was investigated as a function of pH and protein: starch ratio. OSA-modified starch tended to interact with heated WPI (HWPI) rather than non-heated WPI (NWPI), and the optimum conditions for their complexation were a protein: starch ratio of 1:10 and pH 4.5, probably driven by both electrostatic and hydrophobic interactions. The effects of the degree of substitution (DS) and molecular weight (Mw) of OSA-modified starch on the properties of the complexes formed under the optimum conditions were investigated using absorbance measurements (at 515 nm). Soluble complexes (HWPI-OSA SC) between 0.5% (w/v) HWPI and 5% (w/v) OSA-modified starch with a Mw of 19.24 ± 0.07 × 10 4 g/mol and a DS of 4.29 ± 0.11% could be formed at pH 4.5. The structure of HWPI-OSA SC was examined using transmission electron microscopy (TEM), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Characterization of the HWPI-OSA SC revealed that the intermolecular interactions between HWPI and OSA-modified starch led to their different characteristics from HWPI and OSA-modified starch alone.